A New Derailment Detection Method of Rail Vehicles. Issue 1 (1st November 2022) - Tao, Qiang; Sun, Xiaojie; Liu, Yi; Dai, Chenxi; Zhao, Yulun
Abstract: Aiming at the problem of train derailment detection, researchers at domestic and abroad mainly focus on the derailment coefficient and wheel load reduction rate, but the derailment coefficient and wheel load reduction rate can't accurately reflect the status of rail vehicle derailment in time. In this paper, a new derailment detection method of rail vehicles is designed based on the lateral acceleration and roll angle as the key characteristic physical quantities of wheelset derailment. Firstly, the virtual simulation method is used to grasp the characteristics of the key physical quantities. Then, the appropriate scheme of derailment detection system is proposed to measure the key characteristic physical quantities and judge whether the rail vehicle is derailed. Finally, the simulation data is used to prove the effectiveness of the detection method, which can lay the foundation for the practical engineering application.